Legal Issues Concerning Compulsory COVID-19 Vaccination: Nigeria as a Case Study - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Mulegi, Tom; Eregbuonye , Obieshi (Manunggal Halim Jaya, 2024)
It is no news that COVID-19 has rendered severe havoc in the global environment. Although, various medical scientists and scholars were able to find a possible curtailment (Through vaccination) of the deadly COVID-19, however, there seems to be fear of the negative medical outcome of being vaccinated with the COVID-19 vaccine, given several claims of the potential danger. Furthermore, it suffices to state that Nigeria has also had its fair share of the COVID-19 pandemic. In this regard, to curtail the spread of COVID-19 in Nigeria, the Nigerian government sorts to make vaccination compulsory, despite the legal and medical rights of its citizens as enshrined in the constitution and judicial precedent. It is in this regard, that this study sort to adopt a hybrid method of study concerning the legal issues of compulsory vaccination in Nigeria. Concerning this, 310 questionnaires were sent to respondents residing in Nigeria. The study therefore found that there were incidences of COVID-19 in Nigeria and there are laws concerning the control of infectious disease in Nigeria. However, the study further found that it is a legal misnomer to compel an individual forcefully against his/her wishes to be vaccinated. Therefore, the study concludes and recommends that for effective vaccination against COVID-19, the Nigerian government needs to avoid forceful vaccination, but rather a wide sensitization concerning the vaccine's potency as against the negative claim concerning the COVID-19 vaccine.